Formation of Russian magistracy: implementation of the digital economy requests in the educational process - E. V. Voevodina (Цифровая социология)
The state of Russian magistracy in the transition to a digital economy has been studied. Some aspects of Russia’s accession to the Bologna process have been affected – problems of transition associated with a lack of understanding of the essence of transformations by the main stakeholders have been noted. The issues of socialization of students of the «digital» generation have been analyzed, the most characteristic of them – the desire for constant change, intolerance of the same type of problems, good knowledge of information technology. It has been noticed, that Russian magistracy is faced with the need to adapt to the needs of the digital economy, as well as the «generational» characteristics of representatives of generation Z.The results of an empirical sociological study “Birth of a Russian magistracy”, carried out as part of the project of the Higher School of Economics Institute of Education, have been presented. The purpose of this study is to analyze the state of modern Russian magistracy and define key processes in which the main Acknowlegements. The article reflects the results of the research in the framework of the project “Birth of the Russian master’s degree”, implemented by the HSE Institute of education, the winner of the Vladimir Potanin Scholarship program of The V. Potanin Charitable Foundation. © The Author(s), 2019. This is an open access article under the CC BY 4.0 license (http://creativecommons.org/licenses/by/4.0/). stakeholders (students, teachers and employers) are involved. The results of a survey of teachers of magistracy (713) in Russian regions, as well as undergraduates (1 140), have been reflected in the article. As the main results, information on the use of modern educational technologies in the preparation of Russian undergraduates has been given – a conclusion has been made about the small distribution of on-line education and network programs in universities.The research data characterizing the degree of digital competencies of Russian graduate students have been adduced: information search and processing, use of IT technologies, information security, ability to work with «big» data. It has been noted, that these skills are well developed among modern students, but the participation of universities in their development is low. It has been concluded, that Russian magistracy is characterized by a «transitional» period in solving the problems of the digital economy.